THREE MEGA TRENDS SUPPORTING THE ASIAN CENTURY – DEMOGRAPHICS, URBANISATION AND DIGITAL REVOLUTION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, May 2016 The campus community as well as the public were recently treated to another series of International Public Lecture, this time by a Senior Economist from the Japan Research Institute, Dr. Keiichiro Oizumi, who shared his views on three mega trends supporting the Asian Century (referring to the 21 century), namely demographic transition, urbanisation and digital revolution.